Sero-prevalence of transfusion transmissible infections among 59,434 blood donors over a period of 5 years in a tertiary care institute in Himachal Pradesh - Sood, Shivani; Malhotra, Sandeep; Taggar, Gurpreet K.; Sood, Pranav (International Journal of Research in Medical Sciences, 2025)
Background: Blood transfusion is the cornerstone of modern health services. Each blood component transfused has a potential risk of transfusion transmissible infections. Frequent assessment of the prevalence of these infections among blood donors is essential to assess the risk and to improvise the testing methods accordingly. This study was undertaken in Department of Immunohematology and Blood Transfusion, Indira Gandhi Medical College (IGMC), Shimla to assess the sero-prevalence and trends of human immunodeficiency virus (HIV), hepatitis B surface antigen (HBsAg), and hepatitis C virus (HCV), among blood donors who donated blood from 2020 till 2024. Methods: Enzyme-linked immunosorbent assay (ELISA) testing for HIV, HBsAg and HCV was carried out on all blood samples from voluntary and replacement blood donors and results were recorded in Microsoft Office Excel sheet. Results: Out of 59,434 blood units collected, 558 units tested positive for HIV, HBsAg and HCV. The individual sero-positivity rates were 0.44% (263 cases) for HCV, 0.41% (241 cases) for HBsAg, 0.08% (50 cases) for HIV. There were 2 cases of co-infections of HBsAg with HCV, 1 case of co-infection of HIV with HBsAg and 1 case of co-infection of HIV with HCV. A rising trend of HIV and dual sero-positivity among blood donors was noted in the study. Conclusion: The alarming rise in the prevalence of transfusion transmissible infections (especially dual positivity) among blood donors’ stresses upon the need for strict adherence to donor selection criteria and using better screening technologies like chemiluminescence immunoassay (CLIA) and nucleic acid amplification testing (NAT) to detect window phase infective blood.